2007 9th International Conference on Transparent Optical Networks 2007
DOI: 10.1109/icton.2007.4296248
|View full text |Cite
|
Sign up to set email alerts
|

Bound Whispering Gallery Modes in Circular Arrays of Dielectric Spherical Particles

Abstract: Low-dimensional ordered arrays of optical elements can possess bound modes having an extremely high quality factor. Typically, these arrays consist of metal elements which have significantly high light absorption thus restricting performance. In this paper we address the following question: can bound modes be formed in dielectric systems where the absorption of light is negligible? Our investigation of circular arrays of spherical particles shows that (1) high quality modes in an array of 10 or more particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(55 citation statements)
references
References 20 publications
4
51
0
Order By: Relevance
“…Following from our estimates for circular arrays, 12 the dipolar approach is quite accurate in all cases of interest for the linear chain as well since estimates for multipole interactions up to n max =3 have been considered. We found that if the refractive index exceeds 2, then the corrections to the resonance frequency are less than 2%.…”
Section: The Multisphere Mie Scattering Formalism In the Study Of Parmentioning
confidence: 99%
See 4 more Smart Citations
“…Following from our estimates for circular arrays, 12 the dipolar approach is quite accurate in all cases of interest for the linear chain as well since estimates for multipole interactions up to n max =3 have been considered. We found that if the refractive index exceeds 2, then the corrections to the resonance frequency are less than 2%.…”
Section: The Multisphere Mie Scattering Formalism In the Study Of Parmentioning
confidence: 99%
“…4 can be therefore understood as the consequence of its small difference from the threshold value. Since corrections to the transversal mode resonant wavevector k were estimated to be around 2% 12 it is not clear whether our preliminary conclusion about longitudinal modes in ZnO would remain valid after more accurate study.…”
Section: Investigation Of Particle Chainsmentioning
confidence: 99%
See 3 more Smart Citations